Assessment of Vitamin A Status of Preschool Children in a Sub-Saharan African Setting: Comparative Advantage of Modified Relative-dose Response Test (Journal of Health, Population and Nutrition, 2010)
A nationally-representative sample of 2,696 preschool children living in Congo was examined during August- September 2003 to determine the rates of vitamin A deficiency. Ninety clusters of 30 children, aged six months to six years, were selected, using a randomized two-level cluster-sampling method. Vitamin A deficiency was determined by assessing the prevalence of active xerophthalmia (night-blindness and/or Bitot spots) in the cross-over sample of 2,696 individuals. A semi-quantitative seven-day dietary questionnaire was concurrently applied to the mothers of children enrolled to estimate the latter's consumption of vitamin A-rich food. Vitamin A status was assessed by performing the modified relative dose-response test (MRDR) on dried blood spots (DBS) from a subsample of 207 children aged less than six years and the impression cytology with transfer (ICT) test on a subsample of 1,162 children. Of the children enrolled, 5.2% suffered from night-blindness, 8.0% had Bitot spots, and 2.5% had other vitamin A deficiency sequellae. Fifty-three percent of the ICT tests showed the presence of vitamin A deficiency. The biochemical MRDR test showed that the vitamin A status of 30% of the study children was critical. Twenty-seven of them had retinol levels of